On the philosophy of logic - Fisher, Jennifer (Thomson wadsworth, 2008)
Jennifer Fisher's ON THE PHILOSOPHY OF LOGIC explores questions about logic often overlooked by philosophers. Which of the many different logics available to us is right? How would we know? What makes a logic right in the first place? Is logic really a good guide to human reasoning? An ideal companion text for any course in symbolic logic, this lively and accessible book explains important logical concepts, introduces classical logic and its problems and alternatives, and reveals the rich and interesting philosophical issues that arise in exploring the fundamentals of logic. THE WADSWORTH PHILOSOPHICAL TOPICS SERIES (under the general editorship of Robert Talisse, Vanderbilt University) presents readers with concise, timely, and insightful introductions to a variety of traditional and contemporary philosophical subjects. With this series, students of philosophy will be able to discover the richness of philosophical inquiry across a wide array of concepts, including hallmark philosophical themes and themes typically underrepresented in mainstream philosophy publishing. Written by a distinguished list of scholars who have garnered particular recognition for their excellence in teaching, this series presents the vast sweep of today's philosophical exploration in highly accessible and affordable volumes. These books will prove valuable to philosophy teachers and their students as well as to other readers who share a general interest in philosophy.